Submerge impingement cooling for the high thermal flux electric board - Ge, Yong An (2019)
Mankind has developed throughout the years, from people living in caves and hunting for food using primitive tools to living in high-rise buildings and surrounded with many man-made luxurious items. This rapid growth in technology has sparked many studies that are impossible to be performed in the past to now being achievable through modern tools. With the recent trend in implementation of nanotechnology, components can now be packed in a more compact manner, hence, reducing the size of many products. However, a coin always has two sides and there are many limitations. Having the ability to be compacted in to a small product leads to a smaller surface area for the dissipation of heat, allowing immense building up of heat to take place. This immense building up of heat increases the temperature of the product, which may result in a significance drop in efficiency and even exceed the melting point of the product, resulting in dire consequences. Therefore, many researches and studies focus on searching for alternatives to better dissipate heat through improving the rate of heat transfer and preventing occurrence of undesired outcomes. The experimental investigations show that direct attention to immersion cooling and submerged jet impingement cooling techniques. Submerged jet outlet velocity, working fluid temperature, submerged jet outlet temperature and nozzle diameter variations are few of the various parameters being examined to determine the relationship they have with the heat flux. The experiments are carried out on the surface of a copper test specimen that is polished with abrasive grinding paper of grit value P2400, where the encounters of bubble formation and the encounter of Critical Heat Flux are being recorded. Further studies on the pattern and arrangement of the jet array for the submerged jet impingement would be greatly anticipated in determining the best pattern and arrangement for submerged jet array impingement.